ANALISIS TINGKAT KOGNITIF SOAL GERAK MELINGKAR BERATURAN DALAM BUKU SMA KELAS X BERDASARKAN TAKSONOMI BLOOM - MUKTAR B. PANJAITAN; NIA T. SILALAHI (JURNAL ILMIAH SIMANTEK, 2022)
This study aimed to determine the percentage of cognitive level distribution on the subject of Regular Circular Motion, threephysics books for class X 2013 curriculum based on Bloom's Taxonomy. This type of research was descriptive qualitativeresearch, and the objects used were three physics books of senior high school students at Class X with Curriculum 2013.The research data was the cognitive level of the questions contained in the book on the subject of Regular Circular Motion.The data analysis in this study was a qualitative descriptive analysis of the data from the validation results and data on thesuitability of the book. Based on the results of research and discussion on the cognitive level of the subject matter of RegularCircular Motion in three physics books of senior high school students at Class X with Curriculum 2013, it was found that thecomparison of the difficulty levels of easy questions (C1-C2), medium questions (C3-C4), and difficult questions (C1-C2) C5-C6) namely: 1). Book I by 6%:84%:10%; 2). Book II of 0%; 84.85%; 15.15%; 3). Book III of 20.93%; 72.1%; 6.98%. From thiscomparison, it can be concluded that the cognitive level in the three physics books studied was not proportional.